2020
DOI: 10.1007/s11214-020-00757-9
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the Pre-Eruptive Magnetic Field Configurations of Coronal Mass Ejections

Abstract: A clear understanding of the nature of the pre-eruptive magnetic field configurations of Coronal Mass Ejections (CMEs) is required for understanding and eventually predicting solar eruptions. Only two, but seemingly disparate, magnetic configurations are considered viable; namely, sheared magnetic arcades (SMA) and magnetic flux ropes (MFR). They can form via three physical mechanisms (flux emergence, flux cancellation, helicity condensation). Whether the CME culprit is an SMA or an MFR, however, has been stro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 342 publications
(486 reference statements)
1
91
0
Order By: Relevance
“…This turns out to be a rather simplistic, and potentially misleading, approach as the high quality and rapid cadence EUV imaging observations have demonstrated. The discovery of EUV waves (Thompson et al, 1999) and post-CME rays (Ciaravella et al, 2002) and their singular connection to eruptive flares (e.g., Long et al, 2017, and references therein) indicated a closer spatial and temporal relation between magnetic energy release and both flare and CME development that previously realized (Longcope and Beveridge, 2007;Qiu et al, 2007); see also Patsourakos et al (2020), and references therein. In my opinion, a paradigm-shifting advance was the identification of the EUV wave driver with a "super-expansion" phase in the very first stages of CME formation .…”
Section: Paradigm Shiftsmentioning
confidence: 90%
See 2 more Smart Citations
“…This turns out to be a rather simplistic, and potentially misleading, approach as the high quality and rapid cadence EUV imaging observations have demonstrated. The discovery of EUV waves (Thompson et al, 1999) and post-CME rays (Ciaravella et al, 2002) and their singular connection to eruptive flares (e.g., Long et al, 2017, and references therein) indicated a closer spatial and temporal relation between magnetic energy release and both flare and CME development that previously realized (Longcope and Beveridge, 2007;Qiu et al, 2007); see also Patsourakos et al (2020), and references therein. In my opinion, a paradigm-shifting advance was the identification of the EUV wave driver with a "super-expansion" phase in the very first stages of CME formation .…”
Section: Paradigm Shiftsmentioning
confidence: 90%
“…Thus, we cannot observe/measure many of the quantities important to coronal energy storage and release, such as magnetic free energy, helicity, or currents. Patsourakos et al (2020) reviewed the subject in detail and put forth a range of ideas for moving forward. • Formation Phase: As discussed earlier, most CMEs undergo their formation and acceleration phases in the inner corona (below 4 Rs).…”
Section: Forecast "Choke Points" and Grand Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Large-scale filament eruptions that drive coronal mass ejections (CMEs) are some of the most spectacular energetic and dynamic transients in the solar corona. A well-known property of CME source regions is that the magnetic free energy required to power a solar eruption is concentrated above radial magnetic field polarity inversion lines (PILs) in the form of stressed, sheared, and/or twisted magnetic field structures (e.g., see Patsourakos et al 2020 and references therein). Pevtsov et al (2012) examined several large-scale filament channels, i.e., long PILs in the underlying photospheric magnetic field distribution with highly sheared coronal magnetic fields, including those without any discernible filament or prominence material, and showed that these types of coronal structures were responsible for slow-to moderatespeed CME events.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the accuracy of PEC reconstructions appears to be a crucial factor for a correct modeling of CMEs. An accurate reconstruction of PECs for observed cases, however, is particularly challenging (Patsourakos et al 2020), since the constraints required for the reconstruction can be inferred only indirectly from, e.g., observed filament shapes or the location of flare arcades or dimmings (e.g., Palmerio et al 2017).…”
Section: Introductionmentioning
confidence: 99%